Foreign languages communicative skills in Secretarial Studies - Guedes, Anabela; Oliveira, Isabel; Santos, Paula; Antunes, Sandra (Universidad de Málaga, 2020)
The aim of the foreign languages teaching is to enable students to further develop and use English language skills in general and specific contexts and this aim is always achieved through the practice of the four skills - reading, writing, listening and speaking. As far as speaking skills are concerned, oral assessment and role-play situations are often used by English teachers to assess students’ skills. Students pursuing a degree in Secretarial Studies and Administrative Assistance at ESTGL and want to become successful administrative professionals must be aware of the importance of English in their future jobs and must be prepared to communicate in real contexts. This paper, using a descriptive humanistic-interpretative methodology, aims to acknowledge that role-play is one technique a language teacher can explore and to substantiate the Communicative Language Teaching approach used in the Bachelor of Secretarial Studies and Administrative Assistance. We concluded that it boosts students’ confidence and their personal interaction skills. and a maximum of 150 words.
Keywords: Lenguas extranjeras - Estudio y enseñanza; Role-play; Interaction; L2 learning; Communicative Language Teaching; Speaking skills